Elastisitas Transmisi Harga Komoditas Buah Pepaya Di Kabupaten Indramayu Jawa Barat - Juri Juswadi; Pandu Sumarna (Paspalum: Jurnal Ilmiah Pertanian, 2022)
This study aims to analyze the elasticity price transmission of papaya fruit at the farmer level (producer) and at the consumer level (retailer) in Indramayu Regency. Papaya is one of the fruits favored by the public because of its vitamin content, fresh taste, and low price. The price transmission elasticity (Et) analysis uses a simple regression between two prices, namely prices at the farm level and at the retailer level. The research data uses time series data on monthly papaya prices at the farmer level and at the consumer level in Indramayu Regency during the 2014-2020 period. The results of the analysis show that the price elasticity of papaya fruit in Indramayu Regency is inelastic (Et < 1). This shows that price changes at the farmer level are smaller than the price changes at the retail level. This means that farmers have not received good prices from traders.